Non-Saponifiable Lipid Composition of Four Salt-Secretor and Non-Secretor Mangrove Species from North Sumatra, Indonesia (Makara Journal of Science, 2012)
Non-saponifiable lipid (NSL) of the fresh leaves and roots from two salt-secretor mangrove species, namely Aegiceras corniculatum (L.) Blanco and Avicennia alba Bl. and two non-secretor mangroves, i.e. Acrostichum aureum L. and Excoecaria agallocha L. was analyzed with special emphasize to triterpenoids and phytosterols. Identification of the triterpenoids and phytosterols was confirmed by comparison of their retention time on the GC column with those of authentic standards and on the interpretation of GC-MS spectra. Triterpenoids and phytosterols comprised the major proportion of NSL. The triterpenoids and phytosterols mainly consisted of 7 and 4 compounds. Triterpenoids were the largest constituent of Ac. aureum and Ae. corniculatum leaves and roots, and E. agallocha roots. In contrast to these triterpenoids-rich species, phytosterols were relatively dominant in the roots of Av. alba. The species of Av. alba and E. agallocha in the leaves were distinguished from the others in that both species contained a larger quantity of phytol. Ae. corniculatum contained a large amount of betulin and α-amyrin in the roots, as well as lupeol in the roots of Av. alba. The diversity in the NSL composition noted with mangrove species in both the leaves and roots suggested that NSL of mangrove leaves and roots can be used as chemotaxonomical character to differentiate species.